Carcinogenic and anticarcinogenic factors in food: symposium - Eisenbrand, Gerhard (Wiley-VCH, 2000)
The relationship between diet and human cancer has been the focus of an international symposium, organized by the Commission on the Evaluation of Food Safety (SKLM) of the Deutsche Forschungsgemeinschaft (DFG). It was held in Kaiserslautern in October 1998. The remarkable results which have been presented by renouned researchers are documented in this book. There is extensive evidence that diet influences the risk of developing cancer due to carginogens and anti-carcinogens in our food. Even though much remains to be understood about the mechanisms, it is now possible to draw consistent conclusions regarding the role of diet, obesity, and alcohol in the etiology of cancer, and to make public health recommendations on the basis of those conclusions. This symposium volume not only provides an overview of our current knowledge on this topic but also points to obvious gaps, it also presents conclusions and recommendations by the SKLM. Thus the SKLM is making available an up-to-date, scientifically substantiated source of information for a wide range of readers and users.
At head of title: "Deutsche Forschungsgemeinschaft
Includes bibliographical references
Made available through Wiley InterScience online books
The DFG Symposium, "Carcinogenic/Anticarcinogenic Factors in Food: Novel Concepts?" was the third in a series of symposia organised by SKLM. Held in Kaiserslautern Oct. 4-7, 1998
Keywords: Konferenzschrift; Bioaktive Verbindungen; Gesunde Ernährung; Krebs; Carcinogen; Ernährung